Adaptive Strategy-Based Digital Entrepreneurship and Capability Analysis for MSME E-Business Performance - Apriyanto Apriyanto; Titik Haryanto; Saefudin Zuhdi; Narrong Hassanee (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The advancement of digital technologies has reshaped competitive structures within small and medium enterprises (SMEs), particularly in Indonesia. Although digital adoption among MSMEs in West Java is high, its application remains largely operational and not fully aligned with strategic managerial practices. This study aims to analyse the influence of Digital Entrepreneurial Orientation (DEO) and Digital Capability (DC) on E-Business Performance (EBP), with Adaptive Strategy (AS) as a mediating variable, to identify key determinants of digital competitiveness among MSMEs. A sequential explanatory mixed-methods approach was employed, beginning with a quantitative phase using Partial Least Squares Structural Equation Modelling (PLS-SEM) on 275 digitally active MSMEs. This was followed by a qualitative phase consisting of in-depth interviews with 12 key informants. The findings reveal that DEO and DC significantly affect EBP, both directly and indirectly through AS. Adaptive Strategy emerges as a pivotal behavioural mechanism that translates digital orientation and capability into improved performance outcomes. Qualitative insights further confirm that digitally successful MSMEs apply iterative learning, analytics-based interpretation, and real-time strategic adjustments in response to algorithmic shifts and market dynamics. The study concludes that digital success is not merely driven by technology adoption but by continuous strategic adaptation. Policy implications suggest the need to strengthen managerial digital competencies and address the urban–rural digital capability gap.